Revitalisasi Tradisi Khotmil Qur’an sebagai Sarana Internalisasi Nilai-Nilai Keagamaan di Masyarakat - Ruslan, Mohammad (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service is a fundamental pillar of the Tri Dharma of higher education, playing a strategic role in bridging academic knowledge with societal realities. This initiative aims to provide concrete contributions through the practical application of religious knowledge that resonates with local cultural contexts. One such effort is reflected in the preservation and revitalization of the Khotmil Qur’an tradition within the community. More than a ceremonial practice, this tradition embodies educational, spiritual, and cultural values that holistically shape religious character. Using a participatory approach, the program actively involves religious leaders, youth, and members of majelis taklim (Islamic study groups) to foster an inclusive and transformative religious atmosphere. The focus lies on integrating routine Qur’anic recitation with contextual interpretation of its meanings, enabling the community not only to read the Qur’an but also to internalize and apply its teachings in daily life. The results of the program show that the Khotmil Qur’an tradition effectively raises collective awareness of the importance of Qur’anic values in reinforcing social ethics, building community solidarity, and strengthening spiritual connections with God. This community service project demonstrates that Khotmil Qur’an can serve as a powerful medium for grounding Islamic teachings in ways that are contextual, practical, and relevant to modern life. Therefore, its continuous preservation deserves support as part of a broader cultural da'wah strategy, aligned with the spirit of Islam as a mercy to all creation.